Catastrophic circulatory collapse after inadvertent subcutaneous injection of treprostinil. (1st June 2018) - Radosevich, John J.; Dutt, Mohan; Feldman, Jeremy
Abstract : Purpose: A case of life-threatening cardiovascular collapse after inadvertent subcutaneous injection of undiluted treprostinil is reported. Summary: A 29-year-old, 76-kg woman with group 1 pulmonary arterial hypertension managed with subcutaneous treprostinil infusion arrived at the emergency department (ED) with headache, nausea, vomiting, and a syncopal episode. Her vital signs were stable on presentation. Admission orders were placed, and the appropriate 3-mL syringe containing 7.5 mg of treprostinil intended for use with the patient's home microinfusion pump was sent from inpatient pharmacy to the ED. The order in the electronic medical record stated to administer treprostinil as a subcutaneous injection rather than an infusion. The patient's nurse transferred the 7.5 mg (3 mL) of undiluted treprostinil to a standard syringe and administered it as a single subcutaneous injection. Within minutes the patient experienced cardiovascular collapse, with a blood pressure nadir of 50/20 mm Hg. Aggressive resuscitation measures were immediately implemented. Initial management included fluids, bolus-dose vasopressors, multiple high-dose vasopressor infusions, ondansetron, acetaminophen, and loperamide. Hemodynamic stability was achieved, and vasopressors were discontinued 16 hours after the overdose event. Subcutaneous treprostinil was restarted at a reduced dose 12 hours after the overdose event and was adjusted to the patient's home dose 24 hours after the initial event. She was discharged in stable condition 30 hours after the overdose event. Conclusion: A patient who received an inadvertent overdose of subcutaneous treprostinil experienced cardiovascular collapse requiring aggressive resuscitation measures. Successful management of the patient was largely supportive, including fluids, bolus-dose vasopressors, multiple high-dose vasopressor infusions, ondansetron, acetaminophen, and loperamide.